Anti-Chlamydia abortus and Anti-Mycobacterium avium subsp. paratuberculosis Antibodies in Buffaloes in the State of Pernambuco, Brazil - Xavier, Amanda de Noronha; do Nascimento, Sérgio Alves; Ortega Sierra, Tania Alexandra; Fernandes de Oliveira, Pollyane Raysa; Mota, Rinaldo Aparecido; Pinheiro Junior, José Wilton (Acta Scientiae Veterinariae, 2019)
Background: The occurrence of economic losses in buffaloes may be related to reproductive problems such as chlamydiosis caused by the bacteria Chlamydia abortus considered as a zoonotic agent; and digestive problems highlighting the infection by Mycobacterium avium subsp. paratuberculosis (Map), responsible for paratuberculosis. There is a little information about these diseases in buffaloes, therefore the aim of this study was to determine the occurrence of anti-Chlamydia abortus and anti- Mycobacterium avium subsp. paratuberculosis (Map) antibodies in water buffaloes in the state of Pernambuco, Brazil. Materials, Methods & Results: The 262 bubaline sera belonging to the serum bank of the Infectious Diseases Laboratory (LIDIC) of the Federal Rural University of Pernambuco (UFRPE) were analyzed. The samples were from nine properties distributed in the municipalities of Agreste and Zona da Mata of the state of Pernambuco. For the detection of anti-Chlamydia abortus and anti-Map antibodies was used a technique of Enzyme immunoabsorption Assay (ELISA) of the IDEXX® by following the manufacturer’s instructions. Regarding the detection of anti-Chlamydia abortus antibodies, it was observed that 47.70% (125/262) of the samples were positive. All properties showed at least one positive animal for the investigation of anti-Chlamydia abortus antibodies. It was also verified the occurrence of 7.25% of suspected animals for the investigation of anti-C. abortus antibodies. No positives animals were observed for Map in the bubaline analyzed. Discussion: The occurrence of anti-C. abortus antibodies in buffaloes in the region can be explained by the fact that properties with buffalo breeding has sanitary management that allows the contact between animals, thus increasing the risk of transmission of the agent. In addition, the variation found from 35% to 68.75% may be associated with divergences to the type of management and breeding system used in each property. The percentage of suspected animals may suggest that the number of positive animals is higher or that there were non-specific reactions with other species of Chlamydia, but it is not possible to determine the seroconversion without the accomplishment of paired serology. Because it is a zoonosis, C. abortus may be a risk to the health of the population involved, since the transmission of the bacteria to humans can occur by contact with secretions and excretions of these animals. No positive animals were found for the occurrence of anti-Map antibodies, however, there are reports of the infection identifying animals with clinical signs or properties with a history of the disease, and this may be related to the differences in each property in relation to the history and sanitary management. Moreover, the ELISA test may not be sensitive to the agent depending on the phase of the infection, because if the response is predominantly cellular, the number of antibodies is diminished, making the serological diagnosis difficult. The use of more sensitive tests for the bubaline species can also favor the diagnosis of the infection. Although the occurrence of anti-Map antibodies in the analyzed samples was not detected, it is important to carry out routine epidemiological studies, since the disease has already been registered in water buffaloes in the state of Pernambuco. Considering the occurrence of anti-Chlamydia abortus antibodies it is suggested to conduct studies in order to isolate the agent and verify its real importance in the reproductive disorders of the bubaline species, since this agent causes reproductive losses and has a zoonotic character.